An evaluation of the efficiencies and priorities for sustainable development in the transportation system for the manufacturing and trade industry - Mariusz Kostrezewski; Katarzyna Wrona (Economic and Environmental Studies (E&ES), 2017)
One of the most important factors in determining sustainable development of using a transport system is in its efficiency, and there are a number of indicators which can be considered to this end. The aim of this paper is to assess and evaluate such efficiencies, their indicators and the extent to which implementing sustainable development and sustainable transportation is feasible within the transportation system within the trade and manufacturing industry. To this end, the authors determine efficiency as a ratio between expenditure and resources, versus the effects of the realised transportation process. The first chapter introduces the transportation system and any specific terms discussed in this paper. The second chapter describes the source material used for the subject of sustainable development and sustainable transportation. The third chapter details the analyses of the transportation system as processed based upon the technical and economic indicators. The penultimate chapter compares existing and proposed alternative logistical solutions for profitability employing heuristically applied methods. And finally, the fifth chapter summarises the calculations and considerations from which the thesis' conclusions are drawn. The authors also propose potential aspects for the development of the areas discussed in this paper.
Keywords: Q01; L91; L99; 330; sustainable development; sustainable transportation; transport system